PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL DENGAN MEDIASI MODAL SOSIAL ( STUDI PADA DINAS KESEHATAN KABUPATEN PATI) (Students' Journal of Accounting and Banking, 2012)
This study aimed to determine the effect of transformational leadership, motivation of organizational commitment mediation with social capital of employees in the Pati District Health Office. It is based on the phenomenon there are some employees who are less concerned with rules of discipline, such as employees to attend morning assembly is only about 40-60% every day, there are about 5% of the employees came absent in the morning but returned before the end of working hours , and there are only focused employees work within their fields without regard to the other terms. A less harmonious relationship between the leadership of the workers were still there. The research was conducted on employees of the Pati District Health Office were 112 people, using census. A statistical technique used is the component matrix test validity, reliability test by Cronbach alpha, multiple regression analysis, F test and test R 2 and adjusted R Square. The results show that transformational leadership has positive and significant impact on employees' social capital in Pati District Health Office. Motivation has positive and significant impact on employees' social capital in Pati District Health Office. Transformational leadership is positive but not significant effect on organizational commitment of employees at the Pati District Health Office. Motivation has positive and significant impact on organizational commitment of employees at the Pati District Health Office. Social capital is positive but not significant effect on organizational commitment of employees at the Pati District Health Office. Social capital does not mediate the effect of transformational leadership and the influence of motivation on organizational commitment of employees in Pati District Health Office. Keywords: Transformational Leadership, Motivation, Social Capital and Organizational Commitment